Penanaman Pohon sebagai Ibadah Sosial: Tinjauan Hadis dan Fikih Lingkungan atas Program Penghijauan Berorientasi Masyarakat - Muhammad Muads Riksa Khaironi; Yasirul Amri; Sucika Elvi Nurbaiti; Intan Miladia Solihah; Rostina Khoirunnisa; Mira Siska; Alfi Syafaah (Wahana Islamika Jurnal Studi Keislaman, 2026)
Contemporary Islamic discourse often frames tree planting as a form of ongoing charity, yet many discussions remain at the level of moral exhortation and do not translate prophetic evidence and environmental jurisprudence into an operational framework for community-based greening programs. This study aims to (1) examine authentic hadith foundations that conceptualize tree planting as sadaqah and a form of social worship through continuous benefits for living beings, (2) analyze how Islamic environmental jurisprudence (fiqh al-bī’ah) constructs principles of public benefit (maṣlaḥah) and harm prevention (mafsadah) in environmental stewardship, and (3) formulate an integrated analytical framework for community-oriented greening programs. The research employs a qualitative library-research design with normative analysis, using thematic hadith materials as primary data and fiqh al-bī’ah, maqāṣid al-sharī‘ah, and contemporary studies on community greening as secondary sources. The findings indicate that hadith provides strong religious legitimacy by linking reward to sustained ecological benefits enjoyed by humans and other creatures, while fiqh al-bī’ah offers evaluative norms to ensure programs maximize maṣlaḥah and minimize harm. Integration yields operational indicators: citizen participation, post-planting maintenance, and equitable distribution of socio-ecological benefits.